Optimization, characterization and heat treatment of TIG-welded AA2219-T87 alloy. Issue 3 (22nd June 2019) - Arunkumar, Sivaraman; Kannan, Thangaraju Deepan Bharathi; Sathiya, Paulraj
Abstract : Among 2000 series aluminum (Al) alloys, AA2219 exhibits excellent weldability and good combination of strength and toughness at very low temperature. This study focused on the optimization of process parameters in tungsten (W) inert gas (TIG) welding of AA2219 using gray relational analysis. The input parameters selected in this work were welding current, voltage and welding speed. Transverse shrinkage, tensile strength and microhardness were measured as performance characteristics. The experiments were conducted in accordance with the L 9 orthogonal array. Analysis of variance was used to assess the significance of the input parameters on the weld quality. The properties were correlated with the help of metallurgical characterization. Postweld heat treatment was done on the optimized weld, and it was observed that heat treatment of the welded samples resulted in a reduction of transverse shrinkage, improvement in tensile strength and increase in microhardness by 30–40%.